Metabolic syndrome and diabetes for the urologist - Fleshner, Neil E.; Bhindi, Bimal (Canadian Urological Association Journal, 2014)
Type 2 diabetes has a number of know urological consequences. Epidemiologic and clinical data suggest a link between metabolic syndrome and prostatic diseases such as benign prostatic hyperplasia (BPH) and prostate cancer. Recent studies have identified metformin as a viable treatment for patients with type 2 diabetes and prostate cancer.